The use of proxemic means of interaction in communication - Koshanova, Ж.Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
In the process of communication, people understand each other not only through spoken language, but also through non-verbal techniques. Verbal techniques are the main source of information, non-verbal ones are the logical, aesthetic, and emotional content of speech, and provide additional information about the communicant. The article discusses such issues as the science of proxemics, the branch of paralinguistics that studies verbal operations, and its place in communication. Proxemics considers spatial communication, its structure and functions that determine the ratio of people depending on their spatial location. The purpose of the study is to show that in the culture of the Kazakh people, first of all, a special place is occupied by the proxemic components of relationships, which are distinctive features of culture, upbringing, conveying the national identity, worldview, and nomadic lifestyle of the people. Based on the research of scientists, the types of distances and their specific features were comprehensively analyzed. Examples related to the verbalization of proxemes in works of art, ways of transmission are also given, their place in the communicative space of the Kazakh people is determined, based on the research conducted, it is proved that these paramals perform the function of linguistic markers.